The Changing Energy Intensity in Indian Economy: A Sector-level Analysis Based on Input-Output Model - Tandon, Anjali; Ahmed, Shahid (International Journal of Energy Economics and Policy, 2016)
This paper is an attempt to analyze changing energy intensities in the Indian economy. The hybrid I-O model at constant prices has been used to address the problem of homogenous pricing of energy inputs across sectors of the economy. Results reveal that the indirect rather than direct energy use is an important source of energy consumption. In such scenario, conservation measures should be pegged in upstream suppliers through technological improvements, fuel substitution or input replacements. Finally, the paper argues that improvements in energy efficiency in the production chains are likely to be more effective than changes within the production process. Keywords: Hybrid Input-Output; Energy intensity; Constant prices JEL Classifications: C67, D57, Q40